Dermatitis Herpetiformis: An Update on Diagnosis And Treatment - Hazlianda, Cut Putri; Putri, Desy Sahara (SCRIPTA SCORE Scientific Medical Journal, 2024)
Introduction: Dermatitis herpetiformis is a relapsing skin disease caused by gluten sensitivity, also known as an extraintestinal manifestation of celiac disease. Methods: This article was made by reviewing 14 articles related to dermatitis herpetiformis which obtained from Pubmed, Science Direct, and Google Scholar. Discussion: Dermatitis herpetiformis is characterized by skin lesions vesicles or exoriated papules intensely itchy or excoriated papules on extensor surfaces, scalp, nuchal area, and buttocks. Dermatitis herpetiformis is primarily diagnosed through direct immunofluorescence of granular IgA deposits. However, modern and recent approaches currently use anti-TG3 antibody levels as the main serological diagnostic marker. Recent studies now confirm strict, long-term gluten free diet as the primary treatment modality. The diet is supplemented with sulfonamides as first line drugs treatment, especially dapsone. Proper diagnosis and management are important to improve the quality of life of the patients. Conclusion: Dermatitis herpetiformis is a skin disease related to hypersensitivity which requires comprehensive approach and treatment. Keyword: Celiac Disease, Dapsone, Dermatitis Herpetiformis, Direct Immunofluorescence, Gluten Free Diet Pendahuluan: Dermatitis herpetiformis, juga dikenal sebagai manifestasi ekstraintestinal penyakit celiac. Metode: Artikel ini disusun dengan meninjau 14 artikel berkaitan dengan dermatitis herpetiformis yang didapatkan pada Pubmed, Science Direct, dan Google Scholar. Pembahasan: Dermatitif herpetiformis adalah penyakit kulit yang ditandai dengan vesikel yang gatal atau papula yang terkelupas. Dermatitis herpetiformis didiagnosis terutama melalui imunofluoresensi langsung deposit IgA granular. Namun, pendekatan modern saat ini menggunakan antibodi anti-TG3 sebagai penanda diagnostik serologis utama. Studi terbaru sekarang mengkonfirmasi diet bebas gluten jangka panjang yang ketat sebagai modalitas pengobatan utama. Diet dilengkapi dengan sulfonamida sebagai pengobatan lini pertama, terutama dapson. Diagnosis dan penatalaksanaan yang tepat penting untuk meningkatkan kualitas hidup pasien. Kesimpulan: Dermatitis herpetiformis adalah penyakit kulit yang berkaitan dengan hipersensitivitas dan membutuhkan pendekatan dan tatalaksana yang komprehensif. Kata Kunci: Dapson, Dermatitis Herpetiformis, Diet Bebas Gluten, Imunofluoresensi Langsung, Penyakit Seliak